White Matter Microstructure in Adolescents and Young Adults With Non-Suicidal Self-Injury - Westlund Schreiner, Melinda; Mueller, Bryon A.; Klimes-Dougan, Bonnie; Begnel, Erin D.; Fiecas, Mark; Hill, Dawson; Lim, Kelvin O.; Cullen, Kathryn R. (Frontiers in Psychiatry, 2020)
Background: Non-suicidal self-injury (NSSI) is a growing public health concern that commonly begins in adolescence, and can persist into young adulthood. A promising approach for advancing our understanding of NSSI in youth is to examine white matter microstructure using diffusion magnetic resonance imaging (dMRI). Method: The present study examined whole-brain group differences in structural connectivity (as measured by global fractional anisotropy [GFA]) between 28 female adolescents and young adults ages 13-21 years with NSSI and 22 age-matched healthy controls (HC). We also explored the association between clinical characteristics including NSSI severity and duration, impulsivity, emotion regulation and personality traits within the NSSI group and GFA of the uncinate fasciculus and cingulum. Results: Compared to the HC group, participants with NSSI had lower GFA in several white matter tracts, including the uncinate fasciculus, cingulum, bilateral superior and inferior longitudinal fasciculi, anterior thalamic radiation, callosal body, and corticospinal tract. When controlling for depressive symptoms, the NSSI group showed an association between NSSI duration (time since initiating NSSI behavior) and lower GFA in the left cingulum. Higher levels of attentional impulsivity were related to lower GFA in the left uncinate fasciculus within the NSSI group. Conclusions: We found evidence suggesting widespread white matter microstructure deficits in adolescents and young adults with NSSI versus HC. We also report inverse associations between white matter integrity and clinical characteristics (duration of NSSI and attentional impulsivity). These white matter microstructural deficits may represent a possible neurobiologically-based vulnerability to developing maladaptive coping mechanisms, such as NSSI. Additionally, results suggest that this white matter disorganization may either worsen with prolonged engagement in NSSI or predict persistent NSSI; thereby highlighting the importance of early intervention targeting this behavior.